ENTREPRENEURIAL INTENTION DETERMINANTS FOR URBAN UNIVERSITY STUDENTS TO CREATE BUSINESS START-UPS: THE IMPACT OF ENTREPRENEURSHIP EDUCATION, PERCEIVED BEHAVIORAL CONTROL, COMMITMENT, AND NASCENT ENTREPRENEURSHIP BEHAVIOR - Indriyarti, Eko Retno; Christian, Michael; Dewi, Yuli Kartika (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
Entrepreneurship is often seen as a pathway to youth empowerment and economic growth, yet start-up failure rates remain high despite the strong entrepreneurial enthusiasm of young people, particularly urban university students. This study investigates the determinants of entrepreneurial intention by incorporating entrepreneurship education, nascent entrepreneurial behavior, perceived behavioral control, and commitment, with commitment also tested as a moderator. Using PLS-SEM with 330 urban university students, the findings reveal that entrepreneurship education, perceived behavioral control, and commitment significantly enhance entrepreneurial intention, while entrepreneurship education also promotes nascent entrepreneurial behavior. However, commitment does not moderate the link between entrepreneurship education and entrepreneurial intention (H3 not supported), and nascent entrepreneurial behavior does not significantly influence entrepreneurial intention (H4 not supported). These results contribute theoretically by extending the Theory of Planned Behavior to the context of urban start-ups and highlighting the boundary conditions of commitment and nascent behavior. Practically, the study underscores the importance of strengthening entrepreneurship curricula and support systems, while cautioning that exploratory entrepreneurial activities alone may not translate into strong start-up intentions. Beyond theoretical contributions, the findings also offer practical insights for Indonesian universities. Specifically, entrepreneurship education should be integrated with project-based learning, mentoring programs, and funding mechanisms that enable students to transform intentions into sustainable ventures within the urban start-up ecosystem.